1992
DOI: 10.1136/bjo.76.9.529
|View full text |Cite
|
Sign up to set email alerts
|

Ocular circulatory changes following scleral buckling procedures.

Abstract: The effect of segmental scleral buckling (SB) on ocular circulation was evaluated by measurements of the ocular pulse amplitude (PA) and the ophthalmic artery pressure (OAP) (Br3' Ophthalmol 1992; 76: 529-531)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
3
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 7 publications
1
23
3
2
Order By: Relevance
“…Yoshida et al 3 demonstrated that the decreased choroidal circulation did not return to the same level as that in eyes that had not undergone surgery until 12 months postoperatively. In our study, the mean period between surgery and measurement of these values in the group that had undergone surgery more than 6 months previously was 4.76 years; this is significantly longer than the postoperative period in the study of Yoshida et al 3 Our results indicated that the CBF after an SB procedure might return to the normal range over the long term; however, the mechanism for this recovery is unclear, and decreases in the choroidal circulatory resistance might be the cause. It is noteworthy that we did not detect the recovery of choroidal circulation after SB until at least 6 months after surgery.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Yoshida et al 3 demonstrated that the decreased choroidal circulation did not return to the same level as that in eyes that had not undergone surgery until 12 months postoperatively. In our study, the mean period between surgery and measurement of these values in the group that had undergone surgery more than 6 months previously was 4.76 years; this is significantly longer than the postoperative period in the study of Yoshida et al 3 Our results indicated that the CBF after an SB procedure might return to the normal range over the long term; however, the mechanism for this recovery is unclear, and decreases in the choroidal circulatory resistance might be the cause. It is noteworthy that we did not detect the recovery of choroidal circulation after SB until at least 6 months after surgery.…”
Section: Discussionmentioning
confidence: 95%
“…3,4,8,10 When the axial length increases, the POBF decreases. 8 There is also a negative correlation between the POBF and the patient's age.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…One study using colour Doppler imaging indicated that scleral buckling procedures with encircling elements decreased average blood flow velocity in the central retinal artery by 35% on the first operative day and by 50% 1 week postoperatively but did not affect that in the ophthalmic artery,7 whereas another study reported that the same surgery reduced the average blood flow velocity in the ophthalmic artery by 31% 2 days after surgery 8. In patients with rhegmatogenous retinal detachment, the ocular pulse amplitude in the surgically treated eyes was reportedly lower by 53% compared with fellow eyes 6 months after scleral buckling 11. These findings suggest that scleral buckling decreases not only retinal but also choroidal and/or optic nerve head (ONH) circulation because the ophthalmic artery is the origin of the arterial branches that supply blood to the eye.…”
mentioning
confidence: 98%
“…[4][5][6][7][8][9][10] The tissue blood flow in the retina or choroid has been noninvasively measured mainly by laser Doppler velocimetry, 4,5 color Doppler ultrasonography, [6][7][8] the laser speckle method, 9 and the pulsatile ocular blood flow technique. 10 However, the evaluation of the retinal blood flow in the macular area by these techniques has been difficult. The Heidelberg Retina Flowmeter (HRF, Heidelberg Engineering, Heidelberg, Germany), which combines the technique of laser Doppler flowmetry with laser scanning technology, can measure the blood flow of retinal capillaries and is less affected by choroidal circulation.…”
mentioning
confidence: 99%